2017
DOI: 10.1039/c7py01743j
|View full text |Cite
|
Sign up to set email alerts
|

Water-soluble fullerene-functionalized polymer micelles for efficient aqueous-processed conductive devices

Abstract: A novel fullerene-based water-soluble conducting micelle has been successfully developed, providing a potential route towards development of aqueous-processed electronic devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…At an aqueous sample concentration of 0.1 mg/mL, DLS revealed that PDMT had an average diameter of 86 ± 18.3 nm (PDI = 0.132) with an average ζ-potential of −16.72 ± 1.17 mV (Figure b), indicating that the presence of hydrophobic tertiary amine groups in PDMT led to formation of nanosized objects. This result also may be attributed to generation of amphiphilic repulsive forces between the hydrophobic polythiophene backbone and hydrophilic tertiary amine side -chains of PDMT, which lead to formation of phase-separated nanoaggregates . Interestingly, after bubbling CO 2 for 60 min, the average diameter and ζ-potential of CO 2 -treated PDMT changed significantly to 138 ± 38.6 nm (PDI = 0.198) and −27.46 ± 0.92 mV, respectively, indicating that CO 2 bubbling remarkably affected the self-assembled structural characteristics and surface charge of PDMT due to formation of charged ammonium bicarbonate in the polymer side chains, which induced larger, aggregated structures.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…At an aqueous sample concentration of 0.1 mg/mL, DLS revealed that PDMT had an average diameter of 86 ± 18.3 nm (PDI = 0.132) with an average ζ-potential of −16.72 ± 1.17 mV (Figure b), indicating that the presence of hydrophobic tertiary amine groups in PDMT led to formation of nanosized objects. This result also may be attributed to generation of amphiphilic repulsive forces between the hydrophobic polythiophene backbone and hydrophilic tertiary amine side -chains of PDMT, which lead to formation of phase-separated nanoaggregates . Interestingly, after bubbling CO 2 for 60 min, the average diameter and ζ-potential of CO 2 -treated PDMT changed significantly to 138 ± 38.6 nm (PDI = 0.198) and −27.46 ± 0.92 mV, respectively, indicating that CO 2 bubbling remarkably affected the self-assembled structural characteristics and surface charge of PDMT due to formation of charged ammonium bicarbonate in the polymer side chains, which induced larger, aggregated structures.…”
Section: Resultsmentioning
confidence: 97%
“…This result also may be attributed to generation of amphiphilic repulsive forces between the hydrophobic polythiophene backbone and hydrophilic tertiary amine side -chains of PDMT, which lead to formation of phase-separated nanoaggregates. 54 Interestingly, after bubbling CO 2 for 60 min, the average diameter and ζ-potential of CO 2 -treated PDMT changed significantly to 138 ± 38.6 nm (PDI = 0.198) and −27.46 ± 0.92 mV, respectively, indicating that CO 2 bubbling remarkably affected the self-assembled structural characteristics and surface charge of PDMT due to formation of charged ammonium bicarbonate in the polymer side chains, which induced larger, aggregated structures. However, after bubbling N 2 for 60 min into the solution previously treated with CO 2 , the average diameter and ζ-potential of PMDT reverted back to a "neutral/nonionic state" (i. e., average diameter = 53 ± 10.6 nm, PDI = 0.126 and ζ-potential = −16.3 ± 0.78 mV), indicating the particle size and surface charge of PDMT undergo reversible changes after bubbling and releasing CO 2 in the aqueous solution.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…On the basis of these molecular weight results, the grafting numbers of the grafted EDOT and the approximate polymerization degree of EDOT in each branch were calculated to be approximately 53/27, 70/14, and 83/14, which are consistent with the 1 H NMR results. In the 13 C NMR spectra (Figures S23, S25, and S27), bands at 125 and 135 ppm originated from the carbon atoms in the thiophene ring of EDOT, whereas the resonance band at 177 ppm originated from the carbonyl carbon atom, indicating that the PEDOT branches were effectively grafted. Size exclusion chromatography coupled to a multiangle laser light scattering (SEC-MALLS) analyses also showed a unimodal molecular weight distribution, giving higher polydispersity index (PDI) values and lower average molecular weights compared to the results from SEC experiment (the typical traces are shown in Figure S34).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…From the standpoint of electrochemical applicability, compared with the linear counterpart, the branched structure has many advantages. The long flexible polymer chains of the copolymer disrupt the intermolecular aggregation and stacking of conjugated segments, therefore imparting solution processability and film-forming characteristics. In other cases, the incorporation of multiple conjugated branches into each copolymer can overcome the problems of limited mechanical durability that arise from a single conjugated polymer that generally has a low molecular weight. , Alternatively, given the significant dissimilarity in the chemical nature between the two distinct polymers types, copolymers have a high tendency to assemble into well-ordered nanostructures, including lamellae and cylinders in the bulk. , This arrangement promotes a denser packing of conjugated polymers in the solid state; conductive domains exhibit an increased number of close contacts within the insulating polymers, which facilitate hopping of electrons between domains. , Therefore, the integration of these individual characteristics is a potentially promising idea for constructing a new π-conjugated polymeric material that also has an optimized optical transparency, flexibility, and improved electronic properties. In this context, several studies on the design of star-shaped copolymers with polythiophene branches have been reported very recently. These multiblock copolymers make use of aliphatic polymer branches to ensure a desirable solubility, which is essential for conventional solution polymerization and characterization, while the star architecture effectively suppresses the interaction of the polythiophene domains.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation